Optimum heat treatment of aluminum alloy used in manufacturing of automotive piston components. Issue 16 (10th December 2018) - Akhtar, Maaz; Qamar, Sayyad Zahid; Muhammad, Muzamil; Nadeem, Ali
ABSTRACT: Many automotive components that were earlier made of cast iron are now using aluminum alloys due to their lower weight, better castability, corrosion resistance, and strength at elevated temperatures. Heat treatment is a major processing step in the manufacturing of aluminum-based piston components. The current paper discusses an optimum heat treatment strategy for AC8H aluminum alloy for improved performance. Solutionizing (for homogenization) is followed by aging at different temperatures. Tensile, impact, and hardness tests are performed on untreated and heat treated specimens. Structural analysis (microscopy) is done to understand the changes in mechanical properties. Fractography is also carried out to identify fracture mechanisms under gradual and impact loads. Yield strength, ultimate strength, hardness, and impact toughness show significant increase when aged at 150°C and 175°C (maximum values of 80 MPa, 177 MPa, 28 HRA, and 5.25 J respectively) but decrease at 200°C. SEM micrographs of fracture surfaces show ductile, brittle, and mixed-mode failure patterns for different samples. Observed structural changes are in line with changes in the mechanical properties. It can be concluded that optimum combination of properties is obtained when specimens are aged at 175°C. These findings are of direct utility for academicians, researchers, and practitioners involved in design and manufacture of automobile and other engineering components.